Improvement of Suboptimal Land Productivity Approach by Land and Plant Management - Marthen Pasang Sirappa; Max Leovold Jhon Titahena (UNIVERSITY OF LAMPUNG, 2014)
Assessment for increasing productivity of suboptimal land with using three kinds of organic fertilizer and six rice varieties had been conducted in the Debowae village, Waeapo district, Buru regency at 2011. Purpose of the assessment were to determine the effect of three types organic fertilizer and the use of six Inpara varieties to growth and productivity of rice in sub-optimal land. Study used a split plot design with three replications (farmers as replicates), where the main plot was three types of organic fertilizers (livestock manure, granular organic, and petroganic), while the subplot was 6 varieties Inpara (Inpara 1, Inpara 2, Inpara 3, Inpara 4, Inpara 5, and Indragiri). The soil types at the study site based on soil classification were Endoaquepts with soil fertility status was low. The study results showed that the use of organic manure combined with inorganic fertilizers, both from livestock manure, while granular organic and petrogranic, gave an average crop growth and yield better than the results obtained by farmers outside of the study. Average petroganic fertilizer had a better growth and higher crop yields compared to other organic fertilizers. The six varieties of rice swamps that were examined (Inpara 1, Inpara 2, Inpara 3, Inpara 4, Inpara 5, and Indragiri) had the average growth and better yields than rice varieties used by farmers outside of the study (2.75 t ha-1). Varieties Inpara 4, Indragiri, Inpara 1 and Inpara 2 had average yield above 7 t ha-1, while Inpara 3 and Inpara 5 average above 4 t ha-1. Combination of granular organic fertilizer with Inpara 4 variety and petroganic with Indragiri variety had the best results (8.37 and 8.02 t ha-1), while the lowest yield (4.48 t ha-1) was reached at combination of livestock manure with Inpara 5 variety.Keywords: adaptive varieties, land and plant management, organic fertilizers, suboptimal land [How to Cite: Marthen PS and MLJ Titahena. 2014. Improvement of Suboptimal Land Productivity Approach by Land and Plant Management. J Trop Soils 19(2): 109-119. Doi: 10.5400/jts.2014.19.2.109]